2021
DOI: 10.1016/j.pmedr.2021.101630
|View full text |Cite
|
Sign up to set email alerts
|

Added sugars, saturated fat, and sodium intake from snacks among U.S. adolescents by eating location

Abstract: Highlights Added sugar, saturated fat, sodium intake higher from snacks eaten at home vs. away. Snacks eaten at home provided about one fourth of daily calories from added sugars. With few exceptions, snack types consumed were similar at home and away from home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…Previous research has found that the majority of snacking intake among U.S. children occurs at home, but it remains unclear if patterns of snacking differ across the day or vary by age group [ 16 , 17 ]. Additionally, grocery stores have been previously identified as the primary food location source (i.e., location from which foods are obtained) of overconsumed nutrients in children’s diets [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that the majority of snacking intake among U.S. children occurs at home, but it remains unclear if patterns of snacking differ across the day or vary by age group [ 16 , 17 ]. Additionally, grocery stores have been previously identified as the primary food location source (i.e., location from which foods are obtained) of overconsumed nutrients in children’s diets [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For adolescents (12–19 years), added sugars intake was also high during dinner in addition to snack occasions in our study. Based on 2009–2016 NHANES data, US adolescents (12–19 years) consumed 2.4 snacks/day on a given day, and most snacks were consumed at home (consuming 1.7 snacks/day at home and 0.7 snacks/day away from home) [ 20 ]. Another study reported that the majority of added sugars consumed by school aged children came from grocery stores, followed by restaurants and school cafeteria in 2003–2010 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the majority of added sugars consumed by school aged children came from grocery stores, followed by restaurants and school cafeteria in 2003–2010 [ 12 ]. Because snacks were commonly consumed by US children [ 20 ] and most added sugars were consumed during snack occasions, intervention strategies may focus on low- or no- added sugars snacks in efforts to reduced added sugars intake, which might have even more impact on children who are high consumers. Schools have made good progress on changing the school environment to support the reduction of added sugars intake among US children intake [ 21 ]; such as by limiting purchases of regular soda or fruit drinks during the school day or on school campuses [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, students tend to prefer to consume light meals rather than large meals. Although the types of snack food consumed at home and away from home were similar, the quantity of added sugars, saturated fat, and salt consumed at home was higher than that consumed away from home (Casey, et al, 2021). College students, who were categorized as adolescents, frequently consumed snack items in between major meals.…”
Section: Introductionmentioning
confidence: 92%